2011
DOI: 10.4097/kjae.2011.61.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided greater occipital nerve block for patients with occipital headache and short term follow up

Abstract: BackgroundThe greater occipital nerve (GON) block has been frequently used for different types of headache, but performed with rough estimates of anatomic landmarks. Our study presents the values of the anatomic parameters and estimates the effectiveness of the ultrasound-guided GON blockade.MethodsThe GON was detected using ultrasound technique and distance from external occipital protuberance (EOP) to GON, from GON to occipital artery and depth from skin to GON was measured in volunteers. Patients with occip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 22 publications
3
39
1
Order By: Relevance
“…However, Choi et al (), also using a Doppler flowmeter, identified the pulsation of the OA at 2.5 cm lateral to the EOP. The distances between the EOP and GON m (#2, 33.5 mm) and between the EOP and GON l (#3, 52.4 mm) were larger than described by Louka set al () or Shim et al (), while the value reported by Tubbs et al () was within the range of our results. The results for females in Arai et al () and Choi et al () were less than the distance between the EOP and OA m (#4, 37.4 mm), but the results for males in Arai et al () were almost the same as the distance between the EOP and OA l (40.8 mm).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, Choi et al (), also using a Doppler flowmeter, identified the pulsation of the OA at 2.5 cm lateral to the EOP. The distances between the EOP and GON m (#2, 33.5 mm) and between the EOP and GON l (#3, 52.4 mm) were larger than described by Louka set al () or Shim et al (), while the value reported by Tubbs et al () was within the range of our results. The results for females in Arai et al () and Choi et al () were less than the distance between the EOP and OA m (#4, 37.4 mm), but the results for males in Arai et al () were almost the same as the distance between the EOP and OA l (40.8 mm).…”
Section: Discussionsupporting
confidence: 72%
“…Loukas et al () and Tubbs et al () reported the GON to be located 2 cm and 4 cm lateral to the EOP, respectively, on the basis of a cadaveric study. The value obtained by Shim et al () using ultrasonography was 23.1 mm on the right side and 20.5 mm on the left. Arai et al (), who examined the position of the OA using a Doppler flowmeter, described the OA as 2.5 cm lateral from the EOP in females and 4.0 cm lateral in males.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the future of scalp block, the use of US guidance can be anticipated with widespread use of ultrasound (US) in the practice of peripheral and selective nerve blockade. Although some components of this block are performed under US guidance [27][28][29], use of US has not become a routine practice in scalp block. The researchers of the current study consider that scalp block will be a safer procedure with the use of US guidance in near future.…”
Section: Discussionmentioning
confidence: 99%
“…The modern "scalp block" in adults is classically described with potential blockade of six nerves including the supraorbital, supratrochlear, auriculotemporal, zygomaticotemporal, greater occipital and lesser occipital nerves [6,[8][9][10][11][12]. This technique has been adapted to children with blocking of both the anterior (supraorbital and supratrocheal nerves) and posterior scalp (greater occipital nerve) with bupivicaine.…”
Section: Anatomy Of "Scalp Block" In Childrenmentioning
confidence: 99%
“…Of note, there have been rare reports of ultrasound use to perform isolated nerve block of the scalp, but no advantage has been established to date over the described classic landmark technique for "scalp block" [11].…”
Section: Posterior Scalpmentioning
confidence: 99%